James Ellroy’s American Tabloid: Conspiracy Theory and Chaos Theory - Isabelle Boof-Vermesse (Sillages Critiques)
As Ellroy himself suggests it in his introduction to American Tabloid, small causes can have portentous effects. Applying determinist chaos theory to the conspiracy that led to the JFK assassination as it is revisited by what is, after all, a fictional text, this essay draws some conclusions as to the opposition between “compartmentalisation” and “connectionism”, on the one hand, and as to the turbulent relationship between history and fiction, on the other.